Notes on TRIMS, investment policy, and competition policy, with special reference to the Caribbean - Odle, Maurice ([s.n.] [S.l.], 1997)
Focuses on the integral relationship between Trade Related Investment Measures (TRIMS) and investment policy and between these two and competition policy. Looks at how these themes relate to Caribbean policy and development objectives.